GR gene polymorphism is associated with inter‐subject variability in response to glucocorticoids in patients with myasthenia gravis. (17th May 2016) - Xie, Y.; Meng, Y.; Li, H.‐F.; Hong, Y.; Sun, L.; Zhu, X.; Yue, Y.‐X.; Gao, X.; Wang, S.; Li, Y.; Kusner, L. L.; Kaminski, H. J.
Abstract : Background and purpose: Glucocorticoids (GCs) are the mainstay treatment of myasthenia gravis (MG). However, wide inter‐individual variability exists in the response to GCs. Methods: A Chinese cohort of 257 MG patients treated with GCs was evaluated for the association between 19 single nucleotide polymorphisms in the GR gene and clinical response to the initial 3 month GC therapy. A quantitative MG score decreasing by ≥3 units or becoming zero was defined as sensitivity to GCs. Results: The rs17209237* G allele was less frequent in the GC insensitive group compared with the GC sensitive group [ P = 0.013, odds ratio (OR) 0.119]. The rs9324921* A allele was more frequent in the GC insensitive group than in the GC sensitive group ( P = 0.046, OR 1.94). Carriers of the rs17209237 G allele were less frequent in the GC insensitive group than in the GC sensitive group (dominant model, P = 0.009). Carriers of the rs9324921 A allele were more frequent in the GC insensitive group than in the GC sensitive group (dominant model, P = 0.037). Multivariate logistic regression revealed that the rs17209237 G allele carrier ( P = 0.037, OR 0.12) and disease duration before GC treatment ( P = 0.011, OR 3.45) were independent factors that contributed to GC efficacy. Conclusion: rs17209237 in the GR gene was identified as an independent factor that contributes to GC efficacy in MG patients. The genetic variations of the GR gene may play a role in predicting response to GC treatment.